Mentalitățile în perioada de tranziție - Doru, Marcel (Calitatea Vieții, 1994)
First of all, the author tries an appropriate definition of the concept of mentality, then fits this concept on the results of an explorative research made upon the specific forms of manifestations of nowadays mentalities.